Considerations with water for turfgrass in arid environments - Whitlark, Brian (Burleigh Dodds Series in Agricultural Science, 2023)
Golf course managers in arid environments must manage every drop of water like it is their last. Water restrictions continue to tighten and water costs are increasing exponentially in many areas. While superintendents in arid environments utilize onsite weather data to schedule irrigation, current research and new technologies offer ways to optimize soil moisture consistency and realize water savings. Courses in California are converting cool season grass to warm season grasses. Despite high conversion costs, the return on investment is typically less than 10 years and 25% or more water savings have been documented at numerous facilities. Significant water savings have been achieved in southern Nevada, California and Arizona though removing irrigated turf and replacing with desert landscape or nativegrasses. Portable soil moisture meters are widely used and inground soil moisture sensors are gaining popularity for use in large turf areas such as fairways and roughs.